Anti-inflammatory, antioxidant and anti-Mycobacterium tuberculosis activity of viridiflorol: The major constituent of Allophylus edulis (A. St.-Hil., A. Juss. & Cambess.) Radlk. (4th November 2016) - Trevizan, Lucas Noboru Fatori; Nascimento, Kamilla Felipe do; Santos, Joyce Alencar; Kassuya, Candida Aparecida Leite; Cardoso, Claudia Andrea Lima; Vieira, Maria do Carmo; Moreira, Flora Martinez Figueira; Croda, Julio; Formagio, Anelise Samara Nazari
Abstract: Ethnopharmacological relevance: The leaves of Allophylus edulis (A. St.-Hil., A. Juss. & Cambess.) Radlk. (Sapindaceae) are traditionally used as a natural anti-inflammatory agent; however, there are no scientific studies demonstrating its activity essential oil. The content of essential oil in A. edulis may be the chemical basis to explain its ethnobotanical uses, since infusions of this plant are used to treat inflammation in the traditional medicine in Brazil. Aim of the study: This study evaluated the anti-inflammatory, antioxidant and anti-mycobacterial activities of the essential oil (EOAE) and viridiflorol, its main compound. Material and methods: Essential oil from fresh leaves of A. edulis (EOAE) was obtained by hydrodistillation in a Clevenger-type apparatus. Forty-one compounds, accounting for 99.10% of the oil, were identified by gas chromatography-mass spectrometry (GC–MS). The major constituent of the oil was viridiflorol (30.88%). Additionally, the essential oil and viridiflorol were evaluated using an in vitro test against Mycobacterium tuberculosis and in 2, 2-diphenyl-1-picrylhydrazyl (DPPH), 2, 2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) assays. Both EOAE (30 and 100 mg/kg) and viridiflorol (3 and 30 mg/kg) by oral administration were assayed in carrageenan-induced mice paw oedema and pleurisy using subcutaneous injection of dexamethasone (0.5 mg/kg) as the positive control. Results: EOAE and viridiflorol displayed moderate in vitro activity in the M. tuberculosis assay. In all tests, EOAE and viridiflorol showed moderate antioxidant activity compared with reference standards. Both EOAE and viridiflorol showed significant inhibition in the carrageenan-induced mice paw oedema via oral administration of the oil (30 and 100 mg/kg), compound (3 and 30 mg/kg), and subcutaneous injection of dexamethasone (0.5 mg/kg, reference drug). Also EOAE and viridiflorol significantly inhibited carrageenan (Cg) induced pleurisy, reducing the migration of total leucocytes in mice by 62±5% (30 mg/kg of oil), 35±8% (100 mg/kg of oil), 71±5% (3 mg/kg of viridiflorol) and 57±3% (30 mg/kg of viridiflorol). Conclusion: For the first time, the results from this work corroborate the literature, showing that A. edulis can be used as a natural anti-inflammatory agent. Moreover, both EOAE and viridiflorol exhibited biological activities, such as anti-mycobacterial, anti-inflammatory and antioxidant activity. Graphical Abstract: